Integrating Situational Leadership and Traditional Values: Enhancing Student Discipline in Islamic Boarding Schools Through Holistic Training Programs - Mujibus Sailin; Masbahuddin; Moh. Rifa’i; Moh Tohet; Fathor Rozi; Ica Maulina Rifkiyatul Islami; Novela Eka Candra Dewi (Communautaire: Journal of Community Service, 2024)
This study focuses on examining the effectiveness of integrating situational leadership with traditional values to enhance student discipline in Islamic boarding schools. The primary objective is to explore how a holistic leadership training program, tailored to the unique cultural context of pesantren, can improve student adherence to school regulations and foster self-discipline. A qualitative case study method was employed, involving in-depth interviews, participatory observations, and document analysis. Data were collected from school administrators, teachers, and students at Nurul Jadid Middle School in Probolinggo, East Java. The findings indicate that the integration of situational leadership principles with the values of pesantren significantly improves student discipline, resulting in a more orderly and conducive learning environment. The study's implications suggest that this model can be adopted by similar institutions to enhance student behavior and academic outcomes. The research contributes to the growing body of literature on educational leadership and discipline, particularly within the context of Islamic education.